Effect of dynamic balance on human mental rotation task in female badminton vs. volleyball players - Amara, Samiha; Al-Hadabi, Badria; El-Ashkar, Heba; Gmada, Nabil; Habacha, Hamdi; Mkaouer, Bessem (Frontiers in Psychology, 2024)
Background The present study aims to compare the mental rotation performance between two non-contact sports (i.e., badminton and volleyball) in different upright conditions (i.e., with and without dynamic balance). Methods Thirty-five female sports and physical education students voluntarily participated in the experiment, including fourteen specialists in badminton and twenty-one specialists in volleyball. The experiment involved a mental body rotation task with or without balance exercises on a wobble board. Results Badminton players outperformed volleyball players in the mental rotation tasks regardless of balance. More interestingly, the results revealed an overall decrease in reaction times when participants performed balance exercises simultaneously with mental rotation. Discussion Our findings suggest that introducing dynamic balance on a wobble board has immediate beneficial effects on the mental rotation performance of female badminton and volleyball players. These findings are discussed in the context of sport specificities and cognitive processing framework.